The role of the neurovascular unit in vascular cognitive impairment: Current evidence and future perspectives - Zhidong He; Jing Sun (Neurobiology of Disease)
Vascular cognitive impairment (VCI) is a progressive cognitive impairment caused by cerebrovascular disease or vascular risk factors. It is the second most common type of cognitive impairment after Alzheimer's disease. The pathogenesis of VCI is complex, and neurovascular unit destruction is one of its important mechanisms. The neurovascular unit (NVU) is responsible for combining blood flow with brain activity and includes endothelial cells, pericytes, astrocytes and many regulatory nerve terminals. The concept of an NVU emphasizes that interactions between different types of cells are essential for maintaining brain homeostasis. A stable NVU is the basis of normal brain function. Therefore, understanding the structure and function of the neurovascular unit and its role in VCI development is crucial for gaining insights into its pathogenesis. This article reviews the structure and function of the neurovascular unit and its contribution to VCI, providing valuable information for early diagnosis and prevention.